Right hemicolectomy with transverse ileus, unscheduled primary end-lateral anastomosis (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
The present research work is qualitative, retrospective, cross-sectional, which seeks to associate the abdominal surgical emergency of the right colon complicated with the right hemicolectomy as an implemented surgical technique. The resection of the ascending colon and part of the transverse colon is known as right hemicolectomy, it is a non-conservative surgical technique used mainly in cases where there is colon cancer, tumor mass, acute appendicitis with large areas of necrosis, diverticula of the cecum and ascending colon, Crohn's disease etc.We review the results obtained in 57 patients who underwent unscheduled primary hemicolectomy and anastomosis in the emergency service of the Abel Gilbert Pontoon Hospital between January 2019 and December 2021. The average age was 27 years, the mortality was 5.2% and one morbidity of 10% (6 cases). It is concluded that right hemicolectomy with primary end-to-side anastomosis is a safe technique.
Keywords: Right hemicolectomy; unscheduled